Development and Effectiveness of a Wrist Flick Training Device to Enhance Volleyball Hitting Performance - Suhairi, Muhammad; Daryanto, Zusyah Porja; Rusdi, Rusdi; Aji, Tri; Basra, Mohd Asmadzy Bin Ahmad (Indonesian Journal of Physical Education and Sport Science, 2026)
Studi purpose. This study aimed to develop and evaluate the effectiveness of a wrist flick training device (Wrist Muscle Flick Training Device /WMFT-Volly) in improving volleyball hitting performance, particularly in enhancing wrist speed and ball control during overhead skills. Materials and Methods. The study employed a research and development approach followed by a pretest–posttest control group experimental design. Thirty university volleyball athletes were randomly assigned to an experimental group (n = 15), which trained using the wrist flick device, and a control group (n = 15), which followed conventional training. The intervention lasted four weeks (12 sessions). Hitting performance (ball speed and accuracy) was measured before and after the intervention. Data were analyzed using the Shapiro–Wilk test for normality, Levene’s test for homogeneity, paired sample t-test, independent sample t-test, and effect size (Cohen’s d). Results. The data were normally distributed and homogeneous (p > 0.05). The experimental group showed a significant improvement in hitting performance (p < 0.05), while the control group did not demonstrate significant changes (p > 0.05). Independent sample t-test revealed a significant difference in gain scores between groups (p = 0.001). The effect size was large (Cohen’s d = 1.20), indicating a substantial practical impact of the intervention. Conclusions. The wrist flick training device is valid, practical, and effective in enhancing volleyball hitting performance. The findings support the importance of specific wrist-focused training as part of an integrated volleyball training program to optimize technical performance.